Proteomic changes to immune and inflammatory processes underlie lung preservation using ex vivo cytokine adsorption - Niroomand, Anna; Hirdman, Gabriel; Pierre, Leif; Ghaidan, Haider; Kjellström, Sven; Stenlo, Martin; Hyllén, Snejana; Olm, Franziska; Lindstedt, Sandra (Frontiers in Cardiovascular Medicine, 2023)
The field of graft preservation has made considerable strides in recent years improving outcomes related to solid organ restoration and regeneration. In lungs, the use of ex vivo lung perfusion (EVLP) in line with devices and treatments has shown promising results within preclinical and clinical studies with the potential to improve graft quality. The benefit of the therapy would be to render marginal and declined donor lungs suitable for transplantation, ultimately increasing the donor pool available for transplantation. Additionally, such therapies used in machine perfusion could also increase preservation time, facilitating logistical planning. Cytokine adsorption has been demonstrated as a potentially safe and effective therapy when applied to the EVLP circuit and post transplantation. The mechanism by which this treatment improves the donor lung on a molecular basis is not yet fully elucidated. We hypothesized that there were characteristic inflammatory and immunomodulatory differences between lungs treated with and without cytokine adsorption, reflecting in proteomic changes in gene ontology pathways and across inflammation-related proteins. In the current study we investigate the molecular mechanisms and signaling pathways of how cytokine adsorption impacts the lung function when used during EVLP and when used post transplantation as hemoperfusion in a porcine model. Lung tissue from EVLP and post lung transplantation were analyzed for their proteomic profile using mass spectrometry. We found through gene set enrichment analysis that inflammatory, immune process, and coagulation pathways were significantly affected by the cytokine treatment both following EVLP and transplantation. In conclusion, we showed that there are molecular mechanisms using a proteomic approach behind the previously reported effects of cytokine adsorption compared to non-treated transplant recipients undergoing EVLP.